TINNITUS AND TEMPOROMANDIBULAR DISORDERS: A LITERATURE DISCUSSION AND CASE REPORT - Alencar Jr., Francisco G. P.; Pope, William (Archives of Oral Research, 2011)
Tinnitus describes the sensation of any sound perceived in the head or in the ears without any evidentstimulus. It may be associated with any form of sensorineural hearing impairment but difficulty in hearingis the major determinant of tinnitus, followed by aging and exposure to noise. Somatic tinnitus is a type ofsubjective tinnitus in which the frequency or intensity is altered by body movements such as clenching thejaw, turning the eyes, or applying pressure to the head and neck. This article reviews the literature aboutthe possible etiologic factors associated with tinnitus, including temporomandibular disorders, while alsopresenting a clinical case in which tinnitus could be associated with myofascial pain. Adequate diagnosisand treatment planning of the clinical case are presented and discussed as well.